PENILAIAN DAMPAK LINGKUNGAN MENGGUNAKAN LIFE CYCLE ASSESSMENT (LCA) PADA PROSES PRODUKSI TEMPE DI SIKS - Apriyanti, Devi; Pratikno, Faishal Arham; Hertadi, Christopher Davito Prabandewa (Jurnal Mitra Teknik Industri, 2025)
The Small-Scale Industrial Zone of Somber (SIKS) serves as a center for tofu and tempeh production, where one of the producers processes approximately 100 kg of soybeans into tempeh daily. The tempeh production process in SIKS contributes significantly to environmental impacts, particularly during the soybean boiling stage, which uses firewood as the primary energy source. The use of firewood generates higher emissions of greenhouse gases such as CH₄, CO₂, and N₂O compared to other types of fuel. This study aims to analyze the environmental impacts of the tempeh production process in SIKS using the Life Cycle Assessment (LCA) method supported by SimaPro software. The analysis results indicate that the boiling stage contributes the highest impact, with a score of 51.5 Pt, mainly due to the use of firewood. As an improvement strategy, a simulation was conducted by replacing firewood with liquefied petroleum gas (LPG), which showed a significant reduction in environmental impact to 4.44 Pt. This strategy also reflects the principle of sustainability by promoting the use of cleaner and more efficient energy sources to reduce the environmental burden. Therefore, the use of LPG is considered effective in reducing environmental impacts in the categories of human health, ecosystem, and resources in the tempeh production process at SIKS.